INTERSECTORAL CONVERSIONS IN REGIONAL ECONOMY - Lyudmila I. Muratova; Andrey E. Safronov (Advanced Engineering Research)
The issues of the intersectoral conversion essence in the regional economy, whereby the economic a c tivities are grouping, are considered. The performance macroeconomic characteristics of the branches and intersec toral co nversio ns of the Russian national economy are analyzed. The natural - resources p o tential role in the gross regional p roduct generation is evaluated.